Arnica montana and its medicinal value in the light of scientific research - Mirosława Krauze-Baranowska; Katarzyna Kimel (Polish Pharmaceutical Society, 2022)
Arnica montana is a plant that has been used in medicine for hundreds of years. Currently it is used in phytotherapy as topical remedies (gels, ointments, liquids with extract from dried arnica flowers) and in homeopathy, in which oral application is also allowed (various dilutions of TM tincture from fresh planta tota). The aim of this work was to summarize the literature data on the importance of arnica and its products in phytotherapy on the background of its homeopathic applications, considering the chemical composition, pharmacological and biological activity, mechanisms of action, and the results of clinical trials. The results of biochemical and pharmacological research confirm the benefits of allopathic arnica products as anti-inflammatory agents. The mechanism of action is mostly based on the presence of two groups of biologically active substances: sesquiterpene lactones - helenalin, dihydrohelenalin and their esters, as well as polyphenolic compounds that enhance their activity. Clinical trials confirm the efficacy of analyzed arnica products in the treatment of muscle-skeletal system disorders of various etiology, including both sport injuries and rheumatic disorders. Additionally, the therapeutic potential of arnica is also associated with other biological activities, especially anti-oedema, anti-rheumatic, antioxidant, and beneficial influence on blood vessels. Recently published papers report also a promising potential of arnica in other indications, including treatment of cutaneous leishmaniasis. The presented review of scientific reports indicates that A. montana products constitute a source of valuable biologically active compounds, and as a result, an effective remedy for inflammatory ailments of different etiology (sport injuries, rheumatic disorders). In addition to the well-established use of arnica as an anti-inflammatory agent, the results of recent years' research expand the therapeutic potential of the plant raw material with new possible applications and directions of action.